Elastic and inelastic scattering of 15N ions by 12C nuclei at energy 81 MeV - А. Т. Rudchik; А. А. Rudchik; О. E. Kutsyk; К. Rusek; K. W. Kemper; E. Piasecki; A. Stolarz; A. Trczinska; Val. М. Pirnak; О. А. Ponkratenko; I. Strojek; E. І. Koshchiy; et al. (Ядерна фізика та енергетика)
ew angular distributions of the 15N + 12C elastic and inelastic scattering were measured at the energy Elab (15N) = 81 MeV. The data were analyzed within the coupled-reaction-channels method (CRC). The elastic and inelastic scattering as well as the more important one- and two-step transfer reactions were included in the channels-coupling scheme. The 15N + 12C double folding-potential (DF) and that of Woods - Saxon form (WS) were used in the CRC-calculations. The WS potential parameters as well as deformation parameters of 12C and 15N were deduced. The contributions of one- and two-step transfers in the 15N + 12C elastic and inelastic scattering channels were obtained. The 15N +12C elastic scatterings data, published previously at energies Elab(15N) = 22 – 31 MeV for the large angles, were also analyzed and energy dependence of the WS potential parameters were deduced. Comparing the data of elastic scattering data of the 15N + 12С and 14N + 12С nuclei and CRC calculations of the 15N + 12С scattering with WS potentials of these two nuclear pares, considerable differences were observed as in the experimental data so in the CRC calculations, especially at the large angles where the transfer reactions contribute to the elastic scattering. By other words, the scattering isotopic effects were observed in scattering of nuclei 15N + 12С and 14N + 12С.